Novel Soliton and Wave Solutions for the Dual-Perturbed Integrable Boussinesq Equation - Akhtar Hussain; Tarek F. Ibrahim; Faizah D. Alanazi; Waleed M. Osman; Arafa A. Dawood; Jorge Herrera (Complexity)
Nonlinear science represents a foundational frontier in scientific inquiry that explores the shared characteristics inherent in nonlinear phenomena. This study focused on the perturbed Boussinesq (PB) equation incorporating dual perturbation terms. Soliton solutions were deduced by leveraging the traveling wave hypothesis. Furthermore, by employing the generalized Jacobi elliptic expansion function (JEEF) method and the improved tan (Λ/2) method, diverse nonlinear wave solutions, including kink, dark, periodic, bright, singular, periodic waves, bell-shaped solitons, solitary waves, shock waves, and kink-shaped soliton solutions, were acquired. The establishment of constraint relations is detailed to delineate the criteria for the existence of these wave solutions. Notably, these solutions are innovative and present novel contributions that have not yet been documented in the literature. In addition, 2D and 3D graphics were constructed to visually elucidate the physical behavior inherent to these newly acquired exact solutions.